2022
DOI: 10.1002/rra.3926
|View full text |Cite
|
Sign up to set email alerts
|

Distributive hydraulic engineering, cross‐scale landscape planning, and climate change resilience: On the water‐adaptive strategy in the Huai'an–Yangzhou Section of China's Grand Canal

Abstract: Water system plays a key role in the coupled human‐nature system, and ancient people's experiences to build a water‐adaptative way of life still shed light on human's pursuit for climate resilience today with their innate traditional ecological wisdom. In this paper, taking the Huai'an‐Yangzhou Section of China's Grand Canal, and particularly its hydraulic engineering system as an example, we show the system's success in addressing the multi‐dimensional challenges in a historical geographical context, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…With the functional value of eliminating floods and improving the efficiency of water resources, water conservancy heritage is the concentrated embodiment of ancient people's water adaptability. L. Y. Xu, Peng, et al (2022) and Y. Q. Xu, Yang, et al (2022) took the Huai'an‐Yangzhou Section of China's Grand Canal, and particularly its hydraulic engineering system, as an example and attributed its success to the advantages brought about by the ‘distributive hydraulic engineering’ approach by the ancient Grand Canal management, compared to the ‘master‐structure dependent’ approach, which appears to be common practice in modern hydraulic engineering. Shi and Zhang (2022) comprehensively examined the flood control heritage of the Yongding River in the late Qing Dynasty associated with the Marco Polo Bridge section, 1890–1899.…”
Section: Historical Evolution Of Human‐water Relationship In the Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…With the functional value of eliminating floods and improving the efficiency of water resources, water conservancy heritage is the concentrated embodiment of ancient people's water adaptability. L. Y. Xu, Peng, et al (2022) and Y. Q. Xu, Yang, et al (2022) took the Huai'an‐Yangzhou Section of China's Grand Canal, and particularly its hydraulic engineering system, as an example and attributed its success to the advantages brought about by the ‘distributive hydraulic engineering’ approach by the ancient Grand Canal management, compared to the ‘master‐structure dependent’ approach, which appears to be common practice in modern hydraulic engineering. Shi and Zhang (2022) comprehensively examined the flood control heritage of the Yongding River in the late Qing Dynasty associated with the Marco Polo Bridge section, 1890–1899.…”
Section: Historical Evolution Of Human‐water Relationship In the Basinmentioning
confidence: 99%
“…The results indicate that there is no inevitable correlation between the level of economic development and the rise and fall of traditional villages. L. Y. Xu, Peng, et al (2022) and Y. Q. Xu, Yang, et al (2022) analyzed the site selection and distribution pattern of Chinese traditional villages along the Yellow River in Shanxi and Shaanxi. Results revealed that site selection and adaptation factors were the result of the area the river covered and the channel density, the distance of the settlement from the river, river width, and river bank shape.…”
Section: Water Adaptability Of Rural Settlements In the Basinmentioning
confidence: 99%
“…The modern sense of landscape planning and also the design, because of industrialization, environmental pollution, general human unreasonable felling of trees, etc. on the modern landscape planning and also design has emerged as a result of the industrialization, environmental pollution and also human's unreasonable cutting down of trees, which have both damaged nature and human's body and mind [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that there are various studies examining the geographical shifting [9], cultural influence [10,11], historical uniqueness [2,3], and infrastructure sustainability of the Grand Canal [12]. The special socio-ecological landscape created by the Grand Canal [13] and the making of the Grand Canal as a heritage site [14] are also highlighted. However, the main focus is still put on the role of the Grand Canal in facilitating regional development via increasing accessibility [4,[15][16][17][18][19], at least in English literature.…”
Section: Introductionmentioning
confidence: 99%